FACILITY DESIGN FOR BENDOSARI ORCHARD EDU-TOURISM BASED ON COMMUNITY PARTICIPATION - Nadlifah, Hindun Khairotun; Andi; Eulis Yulianti Faridah; Paramawardhani, Herninanjati (UIN Sunan Kalijaga, 2023)
Bendosari Orchard and Edu-Tourism stands as an initiative for enhancement and empowerment of Bendosari, Sumbersari, Moyudan, Sleman communities. Unfortunately, since its inception in 2011 and official inauguration in 2017, up until the year 2022, there has been a noticeable absence of development in terms of attractions and amenities. The research employs a qualitative descriptive method, while the planning based on community participation utilizes the Asset Based Community Development approach. This approach advocates for the utilization and empowerment of local assets to create a distinctive experience for visitors. From mapping, planning, implementation/construction, to evaluation together with the community. Beyond physical facilities, there is also a plan for the development of artificial vegetative plant cultivation (grafting, budding, cutting, and topworking). Research outcomes demonstrate that community involvement in the development of the facility resulted in effectiveness at every project phase. These findings provide a concrete example of the importance of community involvement in development projects, which will contribute to the quality and sustainability of project outcomes. The expansion of the tourism area is expected to be sustainable, and one approach is to establish connections with nearby attractions. By doing so, throughout the Bendosari area, tourists will have a variety of options to explore, thereby extending their stay within the Bendosari area, and this distribution will contribute to the local economic growth in the tourism sector.